Stone alive in Lisbon. Audio description and mediation for aesthetic enjoyment in the museum (Cadernos de Sociomuseologia, 2024)
The article aims to promote audio description as an assistive technology resource that enables equitable access to visual information in the context of museums. In addition to briefly outlining the possibilities of constructing audio descriptions based on its basic principles, the text discusses the importance of considering audio description from a perspective that includes the museological experience through the concept of aesthetic accessibility (Alves & Moraes, 2018). To contextualize these reflections, the article includes an account of a mediated visit by students of an introductory course on audio description in exhibitions and museums. The practical activity of the course provided access for visually impaired people to the contemporary art exhibition STONE ALIVE. A Cultural Interpretation of Stone, held at  Museu Geológico de Lisboa. The exhibition, curated by Marta Jecu, was supported by the Center for Interdisciplinary Studies in Education and Development (CeiED) at Lusófona University (ULusófona), the Directorate-General for the Arts (DGArtes), and was part of the Portugal-France 2022 Season.Keywords: Audiodescription. Museums. Cultural Accessibility. Aesthetic Accessibility